Unveiling the water-associated conformational mobility in the active site of ascorbate peroxidase - Chao, Wei-Chih; Lin, Li-Ju; Lu, Jyh-Feng; Wang, Jinn-Shyan; Lin, Tzu-Chieh; Chen, Yi-Han; Chen, Yi-Ting; Yang, Hsiao-Ching; Chou, Pi-Tai (Biochimica et biophysica acta. General subjects, 2018)
We carried out comprehensive spectroscopic studies of wild type and mutants of ascorbate peroxidase (APX) to gain understanding of the conformational mobility of the active site. In this approach, three unnatural tryptophans were applied to replace the distal tryptophan (W41) in an aim to probe polarity/water environment near the edge of the heme-containing active site. 7-azatryptophan ((7-aza)Trp) is sensitive to environment polarity, while 2,7-azatryptophan ((2,7-aza)Trp) and 2,6-diazatryptophan ((2,6-aza)Trp) undergo excited-state water-catalyzed double and triple proton transfer, respectively, and are sensitive to the water network. The combination of their absorption, emission bands and the associated relaxation dynamics of these fluorescence probes, together with the Soret-band difference absorption and resonance Raman spectroscopy, lead us to unveil the water associated conformational mobility in the active site of APX. The results are suggestive of the existence of equilibrium between two different environments surrounding W41 in APX, i.e., the water-rich and water-scant forms with distinct fluorescence relaxation. Our results thus demonstrate for the first time the power of integrating multiple sensors (7-aza)Trp, (2,7-aza)Trp and (2,6-aza)Trp in probing the water environment of a specifically targeted Trp in proteins. [Display omitted] •Trp analogue based fluorescent probes unveil the water associated conformational mobility in APX.•In the presence of N71A mutation, the access of bulky TNS to the heme is impeded by H42-heme ligation.•Subtle changes of water microenvironment around W41 are detected by the newly developed probe (2,6-aza)Trp with higher sensitivity.•Demonstrating the power of integrating multiple sensors in probing the water environment of a targeted Trp in a protein.